Topology Optimization of Phononic Dirac‐Like Cones and Topological Insulators with On‐Demand Operation Frequencies. Issue 6 (5th April 2022) - Chen, Yafeng; Chen, Di; Liu, Baoshou
Abstract: A topology optimization method for designing phononic Dirac‐like cones and topological insulators by achieving the specific modes at specific frequencies is developed. At first, the Dirac‐like cone is created by degenerating one monopolar mode and two dipolar modes at the desired frequency. It is demonstrated that the optimized phononic crystals with Dirac‐like exhibit exotic zero‐index wave manipulation phenomena. Next, by triggering the dipolar and quadrupolar modes simultaneously to form the double Dirac cone and then breaking it to realize band inversion, topological phase transition around the desired frequency is achieved. The robust one‐way edge transport associated with topological phase transition is presented. Abstract : It develops a topology optimization approach for designing phononic Dirac‐like cones and topological insulators. Phononic crystals with Dirac‐like cones at different frequencies are successfully created. Phononic topological insulators with edge states around desired frequencies are designed. Novel phenomena associated with Dirac‐like cones and topological insulators are demonstrated.